Very Large Array Multiband Radio Imaging of the Triple AGN Candidate SDSS J0849+1114 - Peng, Sijia; Li, Zhiyuan; Liu, Xin; Nyland, Kristina; Wrobel, Joan M.; Hou, Meicun (The Astrophysical journal, 2022)
Kiloparsec-scale triple active galactic nuclei (AGNs), potential precursors of gravitationally bound triple massive black holes (MBHs), are rarely seen objects and believed to play an important role in the evolution of MBHs and their host galaxies. In this work we present a multiband (3.0, 6.0, 10.0, and 15.0 GHz), high-resolution radio imaging of the triple AGN candidate, SDSS J0849+1114, using the Very Large Array. Two of the three nuclei (A and C) are detected at 3.0, 6.0, and 15 GHz for the first time, both exhibiting a steep spectrum over 3–15 GHz (with a spectral index −0.90 ± 0.05 and −1.03 ± 0.04) consistent with a synchrotron origin. Nucleus A, the strongest nucleus among the three, shows a double-sided jet, with the jet orientation changing by ∼20° between its inner 1″ and the outer 5.″5 (8.1 kpc) components, which may be explained as the MBH’s angular momentum having been altered by merger-enhanced accretion. Nucleus C also shows a two-sided jet, with the western jet inflating into a radio lobe with an extent of 1.″5 (2.2 kpc). The internal energy of the radio lobe is estimated to be 5.0 × 10 55 erg, for an equipartition magnetic field strength of ∼160 μ G. No significant radio emission is detected at all four frequencies for nucleus B, yielding an upper limit of 15, 15, 15, and 18 μ Jy beam −1 at 3.0, 6.0, 10.0, and 15.0 GHz, based on which we constrain the star formation rate in nucleus B to be ≲0.4 M ⊙ yr −1 .